Building Environmental Awareness: Problem-Based Learning Based on Constructivism - Al Ayyubi, Sholahuddin; Wisudawati, Paed Asih Widi (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
This study aims to explore the potential of integrating Problem-Based Learning (PBL) within a constructivist framework to enhance students' environmental awareness. Employing a descriptive qualitative approach, this research utilizes the Systematic Literature Review (SLR) method to identify, evaluate, and synthesize peer-reviewed literature published between 2020 and 2025. The selection process followed PRISMA guidelines and included academic databases such as Scopus, ScienceDirect, DOAJ, and institutional repositories. A total of 45 articles were initially identified, 20 of which met the inclusion criteria and were analyzed thematically. The findings reveal that the integration of PBL and constructivist approaches contributes significantly to the holistic development of students' ecological knowledge, ethical values, and pro-environmental behaviors. The synergy between both pedagogical models fosters authentic, collaborative, and reflective learning environments, encouraging students to engage with real-world environmental challenges. Thematic analysis indicates that PBL not only enhances cognitive understanding but also supports the internalization of sustainability-oriented attitudes and actions. This integrative strategy is positioned as a promising pedagogical solution to bridge the gap between theoretical knowledge and practical engagement in environmental education. The study offers theoretical contributions by proposing a conceptual framework for environmental learning, and practical implications for educators and policymakers in designing curriculum interventions that are contextually relevant and action-oriented. It advocates for the adoption of PBL as a core instructional model to cultivate environmentally responsible and globally competent learners